Risk factors associated with cognitive dysfunction in patients on peritoneal dialysis: COGNITIVE DYSFUNCTION - Novković Joldić, Mira; Knežević, Violeta; Knežević, Milica (PONS - medicinski časopis, 2025)
Introduction: Cognitive impairments represent a significant global issue, as they deteriorate patients' quality of life, increase mortality and the number of hospitalizations, burden the healthcare system, and raise treatment costs. Aim of procedure: The aim of this research is to determine the prevalence of cognitive dysfunction in patients undergoing peritoneal dialysis. Material and Methods: A cross-sectional study was conducted in May 2024, at the University Clinical Center of Vojvodina, at the  Clinic for
Keywords: cognitive dysfunction, peritoneal dialysis, risk factors